Correlation between Cognition and Quantitative EEG Changes in Patients with Migraine - Abdul Kareem, Raghad A.; Al-Omary , Hanan L. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Migraine is a common debilitating disorder characterized by attacks of mostly unilateral, moderate to severe, throbbing headaches. The diagnosis of migraine is made according to the third edition of the International Classification of Headache Disorders developed by the International Headache Society. There are several types of migraine, the most common of which are migraine without aura and migraine with aura. Objectives: This study aims to find the correlations between quantitative EEG changes and cognition in migraine patients. Methods: The study included 20 migraine patients, 10 during pain attack (ictal phase) and 10 during pain-free period (inter-ictal), in addition to 18 healthy controls. Montreal cognitive assessment and 20-minute scalp EEG were done. After that, four-second epochs were taken from the EEG record to find the power spectral density (PSD) for each of the waves in the range of [delta δ(0.5-4) Hz, theta θ(4-8) Hz, alpha α (8-12) Hz, and beta β (12-30) Hz]. The study was conducted in Al-Shaheed Ghazi Al-Hariri Hospital in Baghdad from October 1, 2022, to May 1, 2023. Results: Quantitative EEG analysis revealed that there is a significant decrease in theta and beta waves in a descending pattern from control to inter-ictal and then to ictal migraine patients, while alpha waves increased in an ascending pattern from control to inter-ictal to ictal migraine patients. In cognition, there was a significant difference between controls and migraine patients in recall memory, language, and abstraction domains. Conclusions: Quantitative EEG findings suggest that alpha waves correlate negatively with cognition, while both theta and beta waves correlate positively with cognitive level.